2018
DOI: 10.1093/sysbio/syy059
|View full text |Cite
|
Sign up to set email alerts
|

A Simulation-Based Approach to Statistical Alignment

Abstract: Classic alignment algorithms utilize scoring functions which maximize similarity or minimize edit distances. These scoring functions account for both insertion-deletion (indel) and substitution events. In contrast, alignments based on stochastic models aim to explicitly describe the evolutionary dynamics of sequences by inferring relevant probabilistic parameters from input sequences. Despite advances in stochastic modeling during the last two decades, scoring-based methods are still dominant, partially due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…This illustrates a fundamental problem with the purely simulationbased LAHP19 approach; running it enough times to sample all cases is impractical. This may be one reason why the authors of LAHP19 limited the maximum gap length G to 50 residues (Levy Karin et al, 2019). A potential solution to this problem would be to use a limited sample to fit a parameteric model, although we have not explored that approach.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This illustrates a fundamental problem with the purely simulationbased LAHP19 approach; running it enough times to sample all cases is impractical. This may be one reason why the authors of LAHP19 limited the maximum gap length G to 50 residues (Levy Karin et al, 2019). A potential solution to this problem would be to use a limited sample to fit a parameteric model, although we have not explored that approach.…”
Section: Resultsmentioning
confidence: 99%
“…LG05 (Löytynoja and Goldman, 2005), RS07 (Redelings and Suchard, 2007), LAHP19 (Levy Karin et al, 2019), and DM20 (De Maio, 2020).…”
Section: Derivation Of Alignment Likelihoods From Indel Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, advances have been made in the development of statistical alignment methods, allowing simultaneous model parameter inference and alignment (Suchard & Redelings, 2006;Novák et al, 2008;Bradley et al, 2009;Nute et al, 2019). Miklós et al (2004) and Levy-Karin et al (2019) have developed the longindel model, in which both indels and substitutions evolve along a phylogenetic tree assuming a joint continuous time Markov process. The rate of indels in this model depends on the indel length.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the problem with tuning alignment parameters, another major shortcoming is that most current programs report a single alignment. Many studies have demonstrated that optimizing an objective function under a specified model of sequence relatedness does not necessarily imply an optimization in homology (Fitch and Smith, 1983; Durbin et al , 1998; Levy Karin et al , 2019; Redelings and Suchard, 2005; Rosenberg, 2009) (see Supplementary notes for a more detailed discussion).…”
Section: Introductionmentioning
confidence: 99%